Detection of IgG antibodies of Brugian filariasis with crude male and female antigens of Dirofilaria immitis - Riyong D. (2014)
Crude antigens from male and female Dirofilaria immitis were used to detect antibody to Brugian filariasis in humans by indirect ELISA. Both antigens were tested with 42 cases of Brugian filariasis, 131 cases of 20 heterologous infections and 35 healthy controls. The results--using male and female antigens--showed sensitivity of 88.1% and 88.1%, and specificities of 64.1% and 51.8%, respectively. Cross-reaction from other helminthic infections using crude male antigen gave false-positives with 48 sera from 13 heterologous diseases at the threshold value of 0.180, while the female antigen gave 63 sera from 15 diseases, at 0.309. Serum antibodies from patients with other helminthic infections--gnathostomiasis, strongyloidiasis, hookworm infections, trichinellosis, capillariasis, angiostrongyliasis, ascariasis, trichuriasis, toxocariasis, neurocysticercosis, cystic echinococcosis, taeniasis and opisthorchiasis--resulted in false-positives with both male and female antigens. One each of sparganosis and paragonimiasis heterotremus sera cross-reacted with only crude female antigen and their OD values were close to the threshold value. Although crude male antigen showed better specificity than crude female antigen, both female and male worms are sources of antigens needed for further purification. This study provides baseline data for further serodiagnosis of Brugian filariasis using dirofilaria antigen.